Negative Diffusion Weighted Imaging on Magnetic Resonance Imaging of the Brain in Creutzfeldt–Jakob Disease - Lackey, Elijah (Case Rep Neurol Med, 2020)
A 76-year-old Caucasian woman initially presented to the Duke Memory Disorders clinic with a 9-month history of a rapid decline in cognitive, motor, and neuropsychiatric function. On initial presentation, the patient required assistance with activities of daily living. On neurological examination, she was found to have Gerstmann's syndrome along with appendicular apraxia. A positional tremor was noted without myoclonus or fasciculations. She had a paucity of speech and was unable to write her own name. Snout and grasp reflexes were present. Episodes of inappropriate laughter were noted during the exam. She was admitted to the inpatient neurology service for further evaluation. The Diffusion Weighted Imaging sequence on Magnetic Resonance Imaging of the brain was negative for restricted diffusion. An electroencephalogram was unremarkable. Cerebrospinal fluid analysis for Real-Time Quaking-Induced Conversion assay was positive along with an elevated 14-3-3 and increased total Tau protein levels. There was no family history of Creutzfeldt–Jakob disease. The cerebral spinal fluid results were consistent with a diagnosis of Creutzfeldt–Jakob disease, despite the negative MRI brain findings.